&ITShort communication&IT:The first report of &ITCyberlindnera rhodanensis&IT associated with clinical bovine mastitis - Dalanezi, Felipe Morales [UNESP]; Paz, Giselle Souza da [UNESP]; Joaquim, Samea Fernandes [UNESP]; Guimaraes, Felipe Freitas [UNESP]; Gimenes Bosco, Sandra de Moraes [UNESP]; Langoni, Helio [UNESP] (Elsevier B.V., 2018)
An acute case of clinical mastitis in a Holstein cow from second lactation is reported here. A milk sample from the affected quarter was cultured on 5% bovine blood agar and incubated at 37 degrees C for 72 h. After 24 h of incubation, numerous colonies of yeast were observed: the Candida characteristic was not detected by CHROMagar Candida (Difco, Franklin Lakes, NJ). The DNA extraction of the isolate was performed, and DNA. was subjected to amplification and sequencing of the D1/D2 region of the large subunit rRNA gene. The sequences were aligned using Mega 7.0 and used for searching GenBank by BLASTn (Basic Local Alignment Search Tool for nucleotides), revealing 98% of identity with Cyberlindnera rhodanensis. To date, this is the first report of this yeast associated with clinical bovine mastitis.
Keywords: yeast; dairy science; milk; intramammary infection